Método para auxílio à seleção de rios urbanos para reabertura: o caso de Curitiba - Arantes, Daniel da Fonseca (2018)
Since most of the planet’s population is in urban centers, the rivers in these areas suffer from urbanization impacts. Efforts to recover these water bodies are increasing in environmental management, with new forms of intervention based on ecological, recreational and landscape planning values, becoming more prominent. The aim of the present work is to propose a method that allows the selection of urban streams for daylighting. A bibliographic review was carried out in order to identify the main criteria applied to several river recovery cases, as well as the main tools applied. The proposed method was tested in the city of Curitiba, indicating the Belém River to be considered for recovery. Moreover, three scenarios were tested in order to identify the best site for a successful daylighting. This work is expected to contribute to the selection process of potential rivers for daylighting and recovery in urban areas.